Stop Talking that Way! An Affective Approach to Uncanny Speech in the Christian College Classroom - Keeley-Jonker, Bethany (Christian scholar's review, 2016)
Bethany Keeley-Jonker and Craig Mattson notice that some of their best speech students practice a delivery so controlled it feels uncanny. This essay traces such “zombie speech” not to students’ worldview assumptions but to affective norms in conventional speech pedagogy. The essay appropriates Christian theology to reorient the practice of speech in keeping with a newly identified value: “immanent publicity.”